Investigating Moroccan EFL Teachers’ Intercultural Sensitivity in Implementing Intercultural Communication Strategies - ELghazoui, Rajaa; Anass, Khadija (International Journal of Language and Literary Studies, 2025)
This study investigates Moroccan EFL teachers’ intercultural sensitivity by implementing Intercultural Communication Strategies (ICS) to enhance students’ cultural awareness. Grounded in Bennett’s (1986) Cultural Sensitivity Theory and Vygotsky’s (1978) Constructivist Learning Theory, the research adopts a quantitative design. Quantitative data were collected using a modified version of the Intercultural Sensitivity Scale (ISS), which assessed five key dimensions: interaction engagement, respect for cultural differences, interaction confidence, interaction enjoyment, and interaction attentiveness. The results indicate that Moroccan EFL teachers demonstrate generally high levels of intercultural sensitivity, particularly in their affective and cognitive dispositions, although some inconsistencies were noted in behavioral engagement. The study concludes that while Moroccan EFL teachers are dispositionally prepared for intercultural pedagogy, sustained institutional support is essential to help translate these attitudes into effective teaching practices. Implications for teacher training, curriculum reform, and policy development are discussed.